2016
DOI: 10.1111/ele.12658
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus accumulates faster than nitrogen globally in freshwater ecosystems under anthropogenic impacts

Abstract: Combined effects of cumulative nutrient inputs and biogeochemical processes that occur in freshwater under anthropogenic eutrophication could lead to myriad shifts in nitrogen (N):phosphorus (P) stoichiometry in global freshwater ecosystems, but this is not yet well-assessed. Here we evaluated the characteristics of N and P stoichiometries in bodies of freshwater and their herbaceous macrophytes across human-impact levels, regions and periods. Freshwater and its macrophytes had higher N and P concentrations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
61
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 137 publications
(77 citation statements)
references
References 61 publications
(79 reference statements)
8
61
1
4
Order By: Relevance
“…Whereas studies of individual or few lakes suggest differences among lakes and regions, spatial patterns are difficult to build from local studies. In particular, our results and another recent paper (Yan et al 2016) demonstrate that N and P cycles are more likely to differ in areas with high human impact; hence, more mechanistic work on N and P cycling in regions with impacted vs. pristine watersheds may identify fundamental differences among regions. We show that key controls on stoichiometry and nutrients vary across study regions with different ecological context, and that the single vs. parallel nutrient response can differ across regions (Fig.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Whereas studies of individual or few lakes suggest differences among lakes and regions, spatial patterns are difficult to build from local studies. In particular, our results and another recent paper (Yan et al 2016) demonstrate that N and P cycles are more likely to differ in areas with high human impact; hence, more mechanistic work on N and P cycling in regions with impacted vs. pristine watersheds may identify fundamental differences among regions. We show that key controls on stoichiometry and nutrients vary across study regions with different ecological context, and that the single vs. parallel nutrient response can differ across regions (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Other recent broad-scale analyses supported the idea that anthropogenic activity might decouple N and P cycles, for example, P accumulates faster than N in lakes that are heavily impacted by humans (Yan et al 2016). This could explain our results from the Northeastern region, where we observed parallel nutrient responses for both nutrient loading and internal processing variables and could not explain variation in stoichiometry.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Nevertheless, a core issue remains: whether the N vs. P scaling exponent is invariably 'constant', or whether its numerical value depends on species functional groupings or other ecosystem properties. Numerous studies have also reported N vs. P scaling relationships with statistically significant variation in the scaling exponent [11,14,15,22,23]. For example, Niklas and Cobb [24] suggested that the scaling exponents of woody and herbaceous species are, on average two-thirds and three-quarters, respectively.…”
Section: Introductionmentioning
confidence: 99%